PENGARUH MEDIA SOSIAL PADA GERNAHA BULAN SUPER BLUE BLOOD MOON - Novi Fitia Maliha (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2018)
Islam responds to natural feomena by presenting a rule of law so that changes that occur in natural phenomena are not a threat or a human life. Lunar eclipse is one of the natural phenomenon that is present at a certain time, not every year occurs and become an interesting natural phenomenon for the community. At this time social media becomes a medium that is effective enough to affect someone against something interesting and rare. The lunar eclipse of 2018 becomes an attraction for the people of the world, one of them Muslim citizens. In general, the lunar eclipse is not known to the public, only astronomers and Islamics astronomers can predict it will happen, but the whole eye is interested in seeing the lunar eclipse